TINGKAT KEMERATAAN JENIS GULMA DI AREAL HUTAN SKUNDER - Naemah, Dina; Fitriani, Adistina; Rachmawati, Normaela; Payung, Damaris (Jurnal Hutan Tropis, 2024)
Undergrowth and weeds function as soil cover, prevent erosion, and provide habitat for various small fauna. The presence of these plants also affects the nutrient cycle and soil quality. Undergrowth have an important role in maintaining the balance of the forest ecosystem. Variations in undergrowth species and density can be influenced by factors such as light intensity, soil moisture, and interactions with other plants. This research underscores the importance of undersgrowth conservation as part of a sustainable forest management strategy. Research was carried out in secondary forests that were established for specific purposes. Data collection was carried out through field surveys involving direct observation, vegetation sampling. Analysis was carried out to identify the type and level of mastery of each type based on the density and frequency of the types that appeared in the observation plots. Apart from inventorying weed types, this research aims to see the diversity and evenness values in the observation area. The findings show that the undergrowth and weeds in secondary forests, in this case the sengon plant (Paraserianthes falcataria) have 17 types belonging to 7 families, the diversity value (H') is 2.35 and the evenness index (E) is 0.83.